2018
DOI: 10.1038/s41591-018-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

The exerkine apelin reverses age-associated sarcopenia

Abstract: Sarcopenia, the degenerative loss of skeletal muscle mass, quality and strength, lacks early diagnostic tools and new therapeutic strategies to prevent the frailty-to-disability transition often responsible for the medical institutionalization of elderly individuals. Herein we report that production of the endogenous peptide apelin, induced by muscle contraction, is reduced in an age-dependent manner in humans and rodents and is positively associated with the beneficial effects of exercise in older persons. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(273 citation statements)
references
References 59 publications
16
232
2
4
Order By: Relevance
“…Thus, it is likely that in aged animals, the ability of exercise to induce pro‐growth and pro‐repair signals is not fully functional. Recent work suggests that this is indeed the case, at least for the exerkine apelin . The authors showed that young but not aged mice or humans increase apelin levels in response to exercise.…”
Section: Stem Cell‐based Interventions In Muscle Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is likely that in aged animals, the ability of exercise to induce pro‐growth and pro‐repair signals is not fully functional. Recent work suggests that this is indeed the case, at least for the exerkine apelin . The authors showed that young but not aged mice or humans increase apelin levels in response to exercise.…”
Section: Stem Cell‐based Interventions In Muscle Agingmentioning
confidence: 99%
“…However, the effects of GDF11 on the muscle and its age‐related changes are still debated, with contradictory reports highlighting the need for further investigation . Another important circulatory factor affecting satellite cell function in sarcopenic muscles is the exercise‐induced myokine apelin . Apelin levels decrease with age, and studies in mice show that this has important consequences for healthspan .…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
See 1 more Smart Citation
“…In the LIFE-Pilot, the endogenous peptide apelin was positively correlated with SPPB score increases with physical activity (r 2 = 0.34; P = .0001). 28 A replication and meta-analysis of the LIFE-Pilot, LIFE, and the Health, Aging, and Body Composition cohort identified several mitochondrial DNA (mtDNA) variants that are associated with variation in walking speed. 29 Another analysis of the LIFE-Pilot and LIFE studies identified mtDNA-encoded variants that are associated with variations in systolic and mean arterial pressure.…”
Section: Biomarkersmentioning
confidence: 99%
“…It is thus imperative to investigate mechanisms accounting for the age‐related muscle loss and functional decline. Changes at all levels, including gene expression, histone modification, DNA methylation, and physical changes in muscle stem cell environment, or niche, have been found to be associated with aging (Liu et al, ; Sahu et al, ; Stearns‐Reider et al, ; Su et al, ; Vinel et al, ; Zykovich et al, ). For instance, one of the studies of gene expression in aging muscle revealed that mitochondrial dysfunction is a major age‐related phenomenon and highlighted the beneficial effects of maintaining a high physical capacity in the prevention of age‐related muscle function decline (Su et al, ).…”
Section: Introductionmentioning
confidence: 99%